2006
DOI: 10.2169/internalmedicine.45.6018
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Polymyxin B-immobilized Fiber Column (PMX) Hemoperfusion Treatment on Acute Exacerbation of Idiopathic Pulmonary Fibrosis

Abstract: Objective This study was aimed to investigate the effect of polymyxin B-immobilized fiber column (PMX) hemoperfusion treatment on the acute exacerbation of idiopathic pulmonary fibrosis (IPF). Patients and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 25 publications
4
75
0
Order By: Relevance
“…Empirically, AE-IPF has been treated with high-dose corticosteroids, antibiotics, and immunosuppressive agents (6-10). However, these agents provide little bene- (15). In the study, four of six patients who were treated with PMX-DHP showed a dramatic improvement in pulmonary oxygenation and survived for longer than 30 days, while later being successfully weaned from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Empirically, AE-IPF has been treated with high-dose corticosteroids, antibiotics, and immunosuppressive agents (6-10). However, these agents provide little bene- (15). In the study, four of six patients who were treated with PMX-DHP showed a dramatic improvement in pulmonary oxygenation and survived for longer than 30 days, while later being successfully weaned from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that direct hemoperfusion with PMX (PMX-DHP) improves oxygenation in patients with acute lung injury or acute respiratory distress syndrome (ARDS), which usually manifests diffuse alveolar damage (12)(13)(14). In addition, PMX-DHP has also been reported to have a beneficial impact in AE-IPF patients on the respiratory status and long-term outcome (15)(16)(17)(18)(19). However, it remains unclear whether PMX-DHP treatment is a useful therapeutic option for AE-IPF.…”
Section: Introductionmentioning
confidence: 99%
“…However, effective treatments are not well-established and mortality of these patients has been reported to be high during the short course (3, 6, (8)(9)(10)(11). Here, we report two cases of acute exacerbation of IP treated with PMX hemoperfusion treatment.…”
Section: Acute Exacerbation Of Idiopathic Pulmonary Fibrosis (Ipf) Ismentioning
confidence: 88%
“…Recently, direct hemoperfusion with a polymyxin Bimmobilized fiber cartridge (PMX-DHP) has been reported to have a beneficial impact on the respiratory status and long-term outcome of patients with AE-IPF (Seo et al 2006;Abe et al 2010;Enomoto et al 2008;Hara et al 2011). Oishi et al reported that proinflammatory, profibrotic, and proangiogenic cytokines, including TGF-β were eluted from PMX fibers used for the treatment of AE-IPF and suggested that adsorption of such cytokines onto PMX fibers might be one of the mechanisms of action involved.…”
Section: Discussionmentioning
confidence: 99%